Basal resource quality and energy sources in three habitats of a lowland river ecosystem. (5th July 2020) - McInerney, Paul J.; Holt, Galen; Lester, Rebecca E.; Thompson, Ross M.; Robson, Barbara; Ryder, Darren S.; Bond, Nick R.; Baldwin, Darren S.; Gawne, Ben; Petrie, Rochelle
Abstract: Understanding energy flow through ecosystems and among sub‐habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats—river channels, anabranches and wetlands—of a lowland river floodplain in the Murray River catchment, Australia during a period of disconnected surface flow. We used a combination of stable isotope and fatty acid analyses to determine which basal resources were assimilated by the backswimmer Anisops thienemanni and the Eastern mosquitofish Gambusia holbrooki and assessed food quality across the three habitats. Seston was a primary basal resource for both animals in all three habitats, but was of higher quality within floodplain habitats than in the river channel. Although floodplain seston contained higher concentrations of essential fatty acids, fatty acid profiles of animals from different habitats remained similar. Our research suggests that inundation of floodplains and subsequent reconnection to the river could be valuable to afford riverine animals the opportunity to access high quality resources, but highlights a need to quantitatively assess the transfer of essential fatty acids between trophic levels to determine how much riverine animals are in fact limited by poorer quality food resources. We demonstrate the importance of estimating the quality of organic matter fluxes into food webs, and the potential role of targeted environmental flows to re‐establish high quality energy pathways in riverine ecosystems.